2018
DOI: 10.1152/ajprenal.00130.2017
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of contrast-induced nephropathy by limb ischemic preconditioning: underlying mechanisms and clinical effects

Abstract: Contrast-induced nephropathy (CIN) is an important complication following diagnostic radiographic imaging and interventional therapy. It results from administration of intravascular iodinated contrast media (CM) and is currently the third most common cause of hospital-acquired acute kidney injury. CIN is associated with increased morbidity, prolonged hospitalization, and higher mortality. Although the importance of CIN is widely appreciated, and its occurrence can be mitigated by the use of pre- and posthydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 118 publications
0
18
0
Order By: Relevance
“…bradykinin, erythropoietin, prostaglandins, nitric oxide, O-linked β-N-acetylglucosamine, and adenosine has been shown to be involved. 25,26 Remote ischemic preconditioning also activates reperfusion injury salvage kinase pathway, endogenous antioxidant system, hypoxia-inducible factor system, suppressing induction of renal inflammation, and preventing renal tubular cell apoptosis. 25 8,15 The sample size for diabetics in the aforementioned study were small and larger trials that assess diabetic patients were needed.…”
Section: Discussionmentioning
confidence: 99%
“…bradykinin, erythropoietin, prostaglandins, nitric oxide, O-linked β-N-acetylglucosamine, and adenosine has been shown to be involved. 25,26 Remote ischemic preconditioning also activates reperfusion injury salvage kinase pathway, endogenous antioxidant system, hypoxia-inducible factor system, suppressing induction of renal inflammation, and preventing renal tubular cell apoptosis. 25 8,15 The sample size for diabetics in the aforementioned study were small and larger trials that assess diabetic patients were needed.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of CIN is not completely known, and therefore, there is no specific treatment for the clinical management of CIN. However, renal parenchymal hypoxia and the generation of reactive oxygen species (ROS) have been reported to play a critical role in the pathogenesis of CIN [4]. Studies based on animal models of CIN have shown that the disturbance of oxygen balance may result in cell apoptosis and necrosis and may manifest as medullary hypoxic injury [5].…”
Section: Introductionmentioning
confidence: 99%
“…The alteration of renal microcirculation due to CM administration is considered a key pathophysiology mechanism of CM-AKI [3]. CM induced a transient and intense renal vasocontraction especially in medulla [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…higher mortality, in addition to increased caregiver burden and higher financial cost [2]. The prophylactic strategies developed to mitigate CI-AKI are largely restricted to pre-and post-hydration protocols and attempts of pharmacological interventions have been disappointing [3].…”
mentioning
confidence: 99%